Theft - Venable, Bill; Terry, W. E., 1921-1992 (Salt Lake City, UT : Project Gutenberg, 2021)
"Theft" by Bill Venable is a whimsical science fiction short story written in the early 1950s. The narrative revolves around an author named Thompson who finds himself in a peculiar situation where he is visited by little green men who provide inspiration for his writing. The story combines elements of humor and fantasy, exploring the thin line between creativity and insanity. As Thompson struggles with writer's block, he encounters these little green figures who assist him in developing engaging and fantastical stories. Initially, he is intrigued by their suggestions, but as the tale progresses, he begins to question their reality. After having produced several stories with their help, Thompson consults a psychiatrist, who ultimately dismisses the little green men as mere hallucinations, convincing Thompson to forget about them. In a surprising twist, however, the psychiatrist himself becomes enamored with the idea of the green men and seeks out their assistance in writing, leading to a humorous conclusion that underscores the theme of creativity and the ever-elusive search for inspiration. (This is an automatically generated summary.)
Release date is 2021-07-19
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Science fiction; Short stories; Authorship -- Fiction